Multimode fiber interferometer with embedded long period grating - Chapalo, Ivan; Theodosiou, Antreas; Kalli, Kyriacos; Kotov, Oleg (My University, 2019)
A multimode fiber interferometer, consisting of two fiber segments and a long period grating (LPG) between them, is investigated. We observe that low order excited modes in the first segment were converted to the broad modal distribution in the second segment utilizing the LPG. The interferometer's signal was measured, when the first and the second fiber segments were subjected to temperature and strain perturbations. On calculating the averaged transfer functions we demonstrated that the interferometer's sensitivity depends on the fiber segment that was subjected to external perturbations. These results confirm the potential of using LPGs in distributed multimode fiber interferometers having external perturbation localization capability.
Keywords: Distributed sensors; Fiber optic sensors; Intermodal interference; Long period gratings; Multimode interferometer; Specklegram sensors